A novel local impedance algorithm to guide effective pulmonary vein isolation in AF patients: preliminary experience among different voltages of atrial substrate. (19th May 2022) - Segreti, L; Maggio, R; De Sanctis, V; Stabile, G; Battaglia, A; Zingarini, G; Mantica, M; Agresta, A; Mazza, A; Pandozi, C; Dello Russo, A; Ottaviano, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recently, a novel technology able to measure local tissue impedance (LI) and contact force (CF) aimed at validating ablation endpoints has become available for clinical use. Purpose: This analysis explores the relationship between LI parameters, substrate characteristics and AF type during ablation in AF patients. Methods: A novel ablation catheter with dedicated algorithm was used to measure LI at the distal electrode. Each ablation point was characterized in terms of RF delivery time, baseline LI and LI drop during ablation according to different voltages (above or below 0.5 mV) of the atrial substrate. Ablation endpoint was PVI as assessed by entrance and exit block with local capture. Data are reported as mean±SD. Results: A total of 2032 RFC deliveries from 34 consecutive patients were analyzed (71% paroxysmal AF, 29% persistent AF). All PVs were successfully isolated with an overall procedure time of 128±33min (fluoroscopy time=15.6±9min, RF delivery time=9.6±4s, CF=11.1±7g). The baseline LI was 155±17Ω prior to ablation and 136±14Ω after ablation (p<0.0001, absolute LI drop of 21.0±8Ω) with a LI drop rate equal to 2.8±2Ω/s. Ablation spots were more frequently deployed in high-voltage areas (>0.5mv, n=1240, 61%). Baseline LI and LI drops were both higher when underlying atrial voltages were >0.5mV than when <0.5mV (156±18Ω vs 153.6±16Ω for starting LI, p=0.0032; 22.2±8Ω vs 19.1±8Ω for LI drop, p<0.0001, respectively). No differences were found in terms of both CF and LI after ablation between >0.5mV and <0.5mV (11.0±7g vs 11.2±7g for CF, p=0.3435; 136.4±13Ω vs 135.3±15Ω for ablated tissue LI, p=0.1521, respectively). Low-voltage areas were more frequently detected at ablated spots in persistent AF cases (n=288, 51.9%) than in paroxysmal AF cases (n=504, 35.1%, p<0.0001), however, no differences were found in terms of both baseline LI and LI drop between persistent and paroxysmal AF cases (156.3±17Ω vs 154.6±17Ω for starting LI, p=0.135; 20.7±8Ω vs 21.1±9Ω for LI drop, p=0.1722, respectively). Conclusions: LI measurements well distinguished contact with high‐voltage areas from low‐voltage areas and were able to detect significant differences in LI drop during ablation according to the voltage level.